PENGARUH LIKUIDITAS, FIRM SIZE, NILAI TUKAR, UTANG LUAR NEGERI TERHADAP KEPUTUSAN HEDGING PADA PERUSAHAAN FARMASI - Mauntina, Kharisma Inzia; Suryati, Suryati (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.06.TAHUN.2025, 2025)
Exchange rate fluctuations are always influenced by uncertainty. To minimize losses in a company, it isnecessery to implement risk management, one of which is Hedging. This study aims to analyze the effect of Liquidity, Firm Size, Exchange Rate, and Foreign Debt on Hedging Decisions in pharmaceutical sector companies listed on the IDX in 2019 2023. The data used are secondary data with data collection techniques in the form of documentation. The method used in this study is a quantitative method and the research sample consists of 20 companies with a total of 100 observation samples. The data analysis used in this study is panel data regression analysis using SPSS 27. Based on the data analysis that has been carried out, it shows that the Liquidity does not have a significant effect on Hedging Decisions. The Firm Size has a positive and significant effect on Hedging. While the Exchange Rate and Foreign Debt have a positive and insignificant effect on Hedging. Referring to the research results, it is recommended that companies with a large operational scale implement a hedging strategy in their companies because large-scale companies face more risk of loss due to market volatility.